PENGARUH TEKNIK WILLIAM FLEXION EXERCISE TERHADAP TINGKAT NYERI HAID (DISMENORE) SISWI KELAS VIII DI SMP N 37 PEKANBARU - Silvia Nora Anggreini; Nia Desriva; Sesy Palupy Ramadhani (Ensiklopedia of Journal, 2022)
Dysmenorrhea is a painful muscle spasm of the uterus that occurs during menstruation. In Indonesia, the incidence of dysmenorrhea is 64.25% consisting of 54.89% primary dysmenorrhea and 9.6% secondary dysmenorrhea. The incidence of dysmenorrhea in Riau among female adolescents in the fifty districts of Pekanbaru City is 85.7%, students have experienced menarche, and 80% of adolescent girls experience pain during menstruation consisting of 25% mild pain, 66.7% moderate pain, 8 , 3% of severe pain and the remaining 20% of young women do not experience pain during menstruation.The purpose of this study was to determine the effect of William Flexion exercise on the level of menstrual pain (dysmenorrhea). This study used the One Group Pre-Test Post-Test Design. The sample size was 16 grade VIII students who experienced menstrual pain (dysmenorrhea) in SMP N 37 Pekanbaru who were selected using purposive sampling technique. Based on the results of the Wilcoxon signed rank test where the p value = 0.001 was smaller than the alpha value (p <0.050) which indicated the effect of the William Flexion exercise technique on the level of menstrual pain (dysmenorrhea) in grade VIII students at SMP N 37 Pekanbaru.